The citizen: an Ubuntu personalism conception - Seale, Wade (Department of Philosophy, 2026)
In this thesis, I argue for an Ubuntu personalism conception of the citizen as a foundationalist account of a grounding for the pluralist political arrangement based on human rights. I start with John Rawls who employed what he called a political conception of the citizen to develop a neutralist theory of justice. In expounding this, I argue that he excluded certain categories of human beings in an unacceptable way, most notably the severely cognitively disabled; and that the neutralism he targeted – his major contribution – is illusive. I then go in search of an alternative grounding for the pluralist political arrangement based on human rights. I explore philosophical personalism as an alternative, identifying major strengths in the intellectual movement for the purposes of grounding the pluralist political arrangement. But I also identify major weaknesses in personalism – in the thought of Juan Manuel Burgos, which is a current, cutting-edge version of personalism; as well as in the thought of the older John Macmurray – an excellent example of social constitution of persons theory. This opens the way for an exploration of Ubuntu personalism. I explore a metaphysical account of Ubuntu, as well as Ubuntu as an ethic, and show how this leads to a socially constituted conception of the person which sits at the intersection of metaphysics and ethics. I say how the citizen is this kind of person and show how it is this conception of the person that best grounds the pluralist political arrangement based on human rights.